Phosphoenolpyruvate carboxykinases as emerging targets in cancer therapy - Yong Yu; Jingying Li; Kaiming Ren (Frontiers in Cell and Developmental Biology, 2023)
Metabolic reprogramming is commonly accompanied by alterations in the expression of metabolic enzymes. These metabolic enzymes not only catalyze the intracellular metabolic reaction, but also participate in a series of molecular events to regulate tumor initiation and development. Thus, these enzymes may act as promising therapeutic targets for tumor management. Phosphoenolpyruvate carboxykinases (PCKs) are the key enzymes involved in gluconeogenesis, which mediates the conversion of oxaloacetate into phosphoenolpyruvate. Two isoforms of PCK, namely cytosolic PCK1 and mitochondrial PCK2, has been found. PCK not only participates in the metabolic adaptation, but also regulates immune response and signaling pathways for tumor progression. In this review, we discussed the regulatory mechanisms of PCKs expression including transcription and post-translational modification. We also summarized the function of PCKs in tumor progression in different cellular contexts and explores its role in developing promising therapeutic opportunities.